The Prognostic Prediction Value of Positive Lymph Nodes Numbers for the Hypopharyngeal Squamous Cell Carcinoma - Pang, Wendu; Luo, Yaxin; Li, Junhong; Cheng, Danni; Rao, Yufang; Mao, Minzi; Qiu, Ke; Dong, Yijun; Liu, Jun; Zou, Jian; Wang, Haiyang; Chen, Fei (Frontiers in Medicine, 2022)
Background The current American Joint Committee on Cancer (AJCC) system only considered the importance of the size and laterality of lymph nodes while not the positive lymph node number (PLNN) for hypopharyngeal squamous cell carcinoma (HPSCC). Methods A total of 973 patients with HPSCC from the Surveillance, Epidemiology, and End Results database (2004–2015) were identified. Univariate and multivariate Cox regression analyses were used to evaluate the prognostic effects. We applied six Cox regression models to compare the survival prognostic values of PLNN and AJCC systems. Results Positive lymph node number showed a significant association with overall survival (OS) and cancer-specific survival (CSS) (P < 0.001) in univariate and multivariable analyses. The increased PLNN of HPSCC gave rise to poor OS and CSS. The survival model incorporating a composite of PLNN and TNM classification (C-index for OS:0.682, C-index for CSS:0.702) performed better than other models. Conclusions A positive lymph node number could serve as a survival predictor for patients with HPSCC and a complement to enhance the prognostic assessment effects of TNM cancer staging systems.